Adenosine diphosphate released from stressed cells triggers mitochondrial transfer to achieve tissue homeostasis. - Hao Li; Hongping Yu; Delin Liu; Peng Liao; Chuan Gao; Jian Zhou; Jialun Mei; Yao Zong; Peng Ding; Meng Yao; Bingqi Wang; Yafei Lu; et al. (PLoS Biology)
Cell-to-cell mitochondrial transfer has recently been shown to play a role in maintaining physiological functions of cell. We previously illustrated that mitochondrial transfer within osteocyte dendritic network regulates bone tissue homeostasis. However, the mechanism of triggering this process has not been explored. Here, we showed that stressed osteocytes in mice release adenosine diphosphate (ADP), resulting in triggering mitochondrial transfer from healthy osteocytes to restore the oxygen consumption rate (OCR) and to alleviate reactive oxygen species accumulation. Furthermore, we identified that P2Y2 and P2Y6 transduced the ADP signal to regulate osteocyte mitochondrial transfer. We showed that mitochondrial metabolism is impaired in aged osteocytes, and there were more extracellular nucleotides release into the matrix in aged cortical bone due to compromised membrane integrity. Conditioned medium from aged osteocytes triggered mitochondrial transfer between osteocytes to enhance the energy metabolism. Together, using osteocyte as an example, this study showed new insights into how extracellular ADP triggers healthy cells to rescue energy metabolism crisis in stressed cells via mitochondrial transfer in tissue homeostasis.